Babar and his children - Brunhoff, Jean de, 1899-1937. (New York : Random House, 1989)
With the birth of triplets, King Babar and Queen Celeste experience the pleasures and pains of parenthood.
Translation of: Babar en famille.
Facsim. Originally published: 1938.
Keywords: Babar (Fictitious character) -- Juvenile fiction; Elephants -- Fiction; Parent and child -- Fiction; Kings, queens, rulers, etc. -- Fiction; Elephants -- Fiction